CLINICO-HISTOPATHOLOGICAL ANALYSIS OF PRE-MALIGNANT AND MALIGNANT LESIONS OF THE INTESTINAL TRACT - BELLAPU, HARITHA; B, ANURADHA; C, SUJATHA; SHAIK, SHAHANUMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The current study’s aim is to correlate clinical variables with histopathological findings of pre-malignant and malignant lesions of the intestinal tract. Methods: The sample size includes all the endoscopic biopsies and surgically resected specimens of the intestinal tract received at the Department of Pathology, S.V. Medical College, Tirupathi for 2 years from November 2016 to October 2018. All the specimens are fixed in 10% formalin and stained with Hematoxylin and Eosin. Special stains and Immunohistochemistry were done wherever required. Results: During the study, we studied 113 specimens of endoscopic biopsies and 759 specimens of surgically resected. Out of 113 endoscopic biopsies, 33 biopsies were premalignant and malignant lesions, among which 8 were premalignat lesions and 25 were malignant. Out of 759 surgically resected specimens, 37 specimens were premalignant and malignant lesions, among which 1 was premalignant and 36 were malignant. Out of 70 lesions, 3 occurred in the small intestine, 59 occurred in large intestine, 8 occurred in the anal canal. In the small intestine, 3 lesions were encountered among which, one each of adenoma, PJP, adenocarcinoma was noted. Out of 59 lesions of large intestine 4 were adenomas, 2 were ulcerative colitis, 48 were adenocarcinoma and its variants, 2 were MANECs, one each of carcinoid and GIST and malignant melanoma were reported. In the anal canal, there were 1 adenoma, 2 mucinous adenocarcinomas, and 5 squamous cell carcinomas reported. A case of adenoma occurred in male patient, among 2 mucinous adenocarcinomas one occurred in female patient and one in male patient. Out of 5 squamous cell carcinomas, 3 occurred in female patients and 2 in male patients. Among 3 lesions of the small intestine, one case each of adenoma, PJP, and adenocarcinoma, all occurred in male patients. 33 out of 48 adenocarcinomas occurred in male patients. The most common symptom was bleeding per rectum (63.83%) followed by constipation, pain in abdomen and diarrhea. The association between Adenocarcinoma and Smoking is not correlated with p=0.67. The association between Adenocarcinoma and Smoking is not correlated with a p=0.38. Conclusion: Most of the neoplasms were from the large intestine followed by the anal canal. The most common neoplasm and also most common malignancy was Adenocarcinoma. Different variants of adenocarcinoma encountered in the study were Mucinous adenocarcinoma and Signet ring cell adenocarcinoma. Adenomas were common in Male patients. Mixed adenoneuroendocrine tumor and gastrointestinal stromal tumor of large intestine were confirmed with IHC study.